2020
DOI: 10.1002/joc.6855
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing spatiotemporal rainfall changes in 1960–2019 for continental Australia

Abstract: Understanding changes in rainfall at a continental scale can inform adaptation and resilience in all sectors that are sensitive to rainfall. This study examined spatiotemporal changes in annual and seasonal rainfall, extreme and nonextreme rainfall, and their probability and intensity over the period from 1960 to 2019 across Australia for six rainfall zones (RZs) using high-quality daily rainfall from 7,593 climate stations. The results revealed statistically significant changes in long-term rainfall, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
(85 reference statements)
1
6
0
Order By: Relevance
“…The most used functions are the Morlet, the Mexican hat, or the Haar (Jiang et al, 2006;Lovejoy & Schertzer, 2012;Mi et al, 2005;Torrence & Compo, 1998). In this study, the Morlet function was used since it was reported in previous works to be appropriate to identify features in geophysical time series (Liu et al, 2020;Sá et al, 1998;Zeri et al, 2019). The function is defined as:…”
Section: Cross-wavelet Analysismentioning
confidence: 99%
“…The most used functions are the Morlet, the Mexican hat, or the Haar (Jiang et al, 2006;Lovejoy & Schertzer, 2012;Mi et al, 2005;Torrence & Compo, 1998). In this study, the Morlet function was used since it was reported in previous works to be appropriate to identify features in geophysical time series (Liu et al, 2020;Sá et al, 1998;Zeri et al, 2019). The function is defined as:…”
Section: Cross-wavelet Analysismentioning
confidence: 99%
“…The occurrence of extreme precipitation events has become more frequent with global climate change, leading to significant human, economic, and societal losses (Liang, 2022). The study of extreme precipitation events has gained worldwide attention with a recent rise in frequency and intensity reported in various regions, including the United States (Gizaw et al, 2021), Japan (Hatsuzuka et al, 2021), Australia (Liu et al, 2020), India (Saha and Sateesh, 2022) and others. Several studies have shown that while extreme precipitation in China follows the global trend, it also exhibits regional and local differences .…”
Section: Introductionmentioning
confidence: 99%
“…However, the predictions for long-term rainfall patterns are far less certain (Giannini et al, 2008;Varanasi et al, 2016). In Australia, it is generally agreed that summer rainfall had increased in eastern Australia over the past century, while winter rainfall had decreased in the southwest, with large decadal-scale variations and distinct changes in different regions (Liu et al, 2020). They further reported an increasing trend in long-term rainfall in Northern and Central Australia, and a decreasing trend across Southern Australia.…”
Section: Discussionmentioning
confidence: 99%